Yonsei Criteria, a Potential Linkage to Intratumoral Foxp3(+)/CD8(+) Ratio for the Prediction of Oncologic Outcomes in Resected Left-Sided Pancreatic Cancer - Hwang, Ho Kyoung (Yonsei Med J, 2020)
PURPOSE: This study sought to investigate associations among Yonsei criteria (tumor confined to the pancreas, intact fascia layer between the distal pancreas and the left adrenal gland and kidney, and tumor located more than 1–2 cm from the celiac axis) and tumor infiltrating lymphocytes in pancreatic cancer. MATERIALS AND METHODS: Patients who underwent curative distal pancreatectomy due to left-sided pancreatic cancer from January 2000 to December 2011 were enrolled. Follow-up was completed September 30, 2015. RESULTS: Fifty patients were enrolled. Having ≥ two metastatic lymph nodes (LNs, p=0.002), intraoperative transfusion (p=0.011), low levels of tumor infiltrating CD8(+) T-cells (p=0.001), and a high Foxp3(+)/CD8(+) ratio (p=0.009) were independent risk factors for disease-free survival. Not satisfying the Yonsei criteria (p=0.021), having ≥ two metastatic LNs (p=0.032), low levels of tumor infiltrating CD8(+) T-cells (p=0.040) and a high Foxp3(+)/CD8(+) ratio (p=0.032) were associated with unfavorable overall survival. High levels of CA19-9 and not satisfying the Yonsei criteria were significantly associated with a high Foxp3(+)/CD8(+) ratio [Exp(β)=3.558; 95% confidence inverval: 1.000–12.658; p=0.050]. CONCLUSION: Yonsei criteria may be clinically detectable biologic marker with which to predict immunologic status and survival in pancreatic cancer patients.